Similitude of a high pressure three-phase fluidized bed subject to foaming - Rudkevitch, Dan (University of Ottawa (Canada), 2007)
Most hydrodynamic models for gas-liquid-solid fluidized beds are developed for atmospheric pressure and they assume that the liquid physical properties, including density, viscosity and surface tension, are sufficient to characterize bubble dynamics. While true for mono-component liquids, multi-component liquids display bubble coalescence inhibition. It is postulated that the hydrodynamic features of a three-phase fluidized bed can be scaled based on geometric similarity and dimensional similitude by matching five dimensionless groups: a liquid Reynolds Number, ReL = ULdPrhoL/micro L; an Archimedes Number, Arp rhoLgdP 3(rhoL-rhoG)/microL 2; a gas-liquid density ratio, rhoG/rhoL; a particle-liquid density ratio, rhop/rhoL; and a superficial velocity ratio, UG/UL. A bubble coalescence index, I, (1 for mono-component liquids and 2 for multi-component liquids) is an empirical means to account for bubble coalescence inhibition. The effects of pressure and surfactants on the hydrodynamics of three-phase fluidized beds, including the phase holdups, dispersed to coalesced bubbling regime transition velocity and minimum liquid fluidization velocity, are evaluated with water and a 0.5%wt aqueous ethanol solution, nitrogen gas, and 2 mm glass beads operated at pressures of 0.1 to 6 MPa. The effect of pressure on the bed phase holdups, in particular the gas holdup, is significant and more pronounced at larger gas flow rates where pressure has a greater effect on the equilibrium bubble size. The addition of ethanol significantly increases the gas holdup and then as pressure is increased, the phase holdups remain relatively constant. The gas holdups in the bed are always lower than those in the freeboard region. Pressure and surfactants both delay the transition from the dispersed to coalesced bubbling regime, more so for the latter.
Keywords: Engineering, Chemical.